The effect of fertilization with dry yeast extract on improving some physical and productive properties of pomegranate trees ( Punica granatum L.) Francy cultivar (Journal of Hama University, 2020)
Study the effect of foliar and soil fertilization with dry yeast extract at concentrations (0, 15, 20 g / l) and combined fertilization (foliar and soil at a concentration of 15 g / l) on some physical properties, fruit set and productivity of pomegranate fruits during the 2019 season, in the following dates: “Beginning of vegetative growth” (When the leaves are complete), after the fruit set full, a month after that .The results showed that fertilization with yeast extract with different treatments and concentrations improved the characteristics of the physical fruits, fruit set and productivity with significant differences compared to the control, where the highest weight of the fruit was 577.8 g in the combined fertilization treatment that outperformed the foliar and soil fertilization treatments, compared to 232.5 g for the control . It also increased the volume of fruits, reaching 617.5 / cm3 compared to the control of 207.5 / cm3. It also increased the weight of the arial (429.7 g), compared to the control 90.5 g, and the number of total and set flowers (306, 149 flowers) increased, compared to the control (230.25 and 80.75 flowers), respectively. Likewise, the percentage of the fruit set (48.85%) and the productivity of the tree (55.3 kg / tree) compared to the control to the percentage of the fruit set (35.05%) and the productivity (17.8 kg / tree).